2017
DOI: 10.1038/srep40943
|View full text |Cite
|
Sign up to set email alerts
|

CD5 molecule-like and transthyretin as putative biomarkers of chronic myeloid leukemia - an insight from the proteomic analysis of human plasma

Abstract: Better and sensitive biomarkers are needed to help understand the mechanism of disease onset, progression, prognosis and monitoring of the therapeutic response. Aim of this study was to identify the candidate circulating markers of chronic-phase chronic myeloid leukemia (CP-CML) manifestations, having potential to develop into predictive- or monitoring-biomarkers. A proteomic approach, two-dimensional gel electrophoresis in conjunction with mass spectrometry (2DE-MS), was employed for this purpose. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…TTR has been previously used in nutritional indexes, due to the association between its plasma levels and the nutritional supply. TTR levels were identified to be decreased in the sera of various cancer types, such as lung, prostate, gastric, ovarian, pancreatic cancer, cholangiocarcinoma and chronic myeloid leukemia (30)(31)(32)(33)(34)(35)(36); therefore, TTR may be considered a potential biomarker. Consistent with these studies, the results from the present study indicated significantly decreased TTR levels in the sera of patients with advanced-stage cervical cancer, compared with the HPV negative normal controls and patients with early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTR has been previously used in nutritional indexes, due to the association between its plasma levels and the nutritional supply. TTR levels were identified to be decreased in the sera of various cancer types, such as lung, prostate, gastric, ovarian, pancreatic cancer, cholangiocarcinoma and chronic myeloid leukemia (30)(31)(32)(33)(34)(35)(36); therefore, TTR may be considered a potential biomarker. Consistent with these studies, the results from the present study indicated significantly decreased TTR levels in the sera of patients with advanced-stage cervical cancer, compared with the HPV negative normal controls and patients with early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these studies, the results from the present study indicated significantly decreased TTR levels in the sera of patients with advanced-stage cervical cancer, compared with the HPV negative normal controls and patients with early-stage cervical cancer. In addition, the TTR levels demonstrated an inverse correlation with tumor volume in gastric and ovarian cancer (32,37), were associated with prostate cancer stage (31) and serve as a therapy-associated biomarker in patients with chronic myeloid leukemia (36). It has been well established that the liver increases the production of positive acute phase reactants and decreases the production of negative acute phase reactants in response to insults, including trauma in the body, inflammation, infection and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The gel pellets showing differentially stained spots in the 2D gels of the control and the tumor samples were excised and the proteins in them were digested with sequencing grade trypsin (Promega, Southampton, UK) as described earlier with slight modifications. The digested peptides extract was analyzed by MALDI‐TOF MS (Ultraflex III, Bruker Daltonics, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, identification of proteins differentially represented in OC tissues compared to normal ovarian tissues can provide potential diagnostic, prognostic, and therapeutic biomarkers and thus, may facilitate in deciding the available treatment choice(s) . Amongst the various proteomic approaches used for biomarker identification, 2D gel electrophoresis (2‐DE) followed by mass spectrometric (MS) identification of the differentially regulated molecules, has customarily been utilized in numerous malignancies …”
Section: Introductionmentioning
confidence: 99%
“…CD5L also acts to downregulate the pathogenicity of Th17 cells [303] . CD5L has been studied as a biomarker and is elevated in serum in chronic leukemia [304] .…”
Section: Discussionmentioning
confidence: 99%